The great conversation : nature and the care of the soul - Lane, Belden C., 1943- (Oxford University Press, 2019)
"The Great Conversation is Lane's multi-faceted treatise on a spiritually centered environmentalism. At the core is a belief in the power of the natural world to act as teacher. In a series of personal anecdotes, Lane pairs his own experiences in the wild with the writings of saints and sages from a wide range of religious traditions. A night in a Missourian cave brings to mind the Spiritual Exercises of Ignatius of Loyola; the canyons of southern Utah elicit a response from the Chinese philosopher Laozi; 500,000 migrating sandhill cranes rest in Nebraska and evoke the Sufi poet Farid ud-Din Attar. With each chapter, the humility of spiritual masters through the ages melds with the author's encounters with natural teachers to offer guidance for entering once more into a conversation with the world."--